The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/rrq.146
|View full text |Cite
|
Sign up to set email alerts
|

What Are Preadolescent Readers Doing Online? An Examination of Upper Elementary Students’ Reading, Writing, and Communication in Digital Spaces

Abstract: The online reading, writing, and communication practices of students have been of significant interest to literacy researchers and teachers throughout the last several years, as insights into what students are currently doing in and outside of school can inform what they can be expected to know and be able to do in digital environments. Yet, little is known about the online activities, perceptions, preferences, and skills of preadolescent students. The present study reports the performance of 1,262 fourth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Recently, however, the reading habits of children and adolescents have changed profoundly. The reason is the advent of digital reading, also known as electronic reading activities or digital texts (Huang, Orellana, & Capps, ; Hutchison, Woodward, & Colwell, ). This form of reading features a wide variety of activities ranging from digital text reading to e‐mail and chat exchanges.…”
Section: What Underlies the Correlation Between Reading Skills And Lementioning
confidence: 99%
“…Recently, however, the reading habits of children and adolescents have changed profoundly. The reason is the advent of digital reading, also known as electronic reading activities or digital texts (Huang, Orellana, & Capps, ; Hutchison, Woodward, & Colwell, ). This form of reading features a wide variety of activities ranging from digital text reading to e‐mail and chat exchanges.…”
Section: What Underlies the Correlation Between Reading Skills And Lementioning
confidence: 99%
“…However, the teens in our study, much like the younger students in Hutchison et al. 's () study, suggested that “using the Internet to consume information was more common than using the Internet to communicate and connect with others online” (p. 449). Although connections were important for the decision to read a text, few of our participants indicated that they shared texts with others on a regular basis or with purpose.…”
Section: Discussionmentioning
confidence: 46%
“…Perhaps because of a failure to acknowledge digital multimodal forms in schools, students today do not acknowledge the digital skills demonstrated outside of school as valuable literacy practices (see Lenhart, Arafeh, Smith, & Macgill, , for a discussion of writing). Further, recent research has highlighted the need to support elementary students’ “abilities to read, write, and communicate online” (Hutchison et al., , p. 18). This teaching tip acknowledges Pokémon GO as a multimodal text that students may be interacting with outside of school and explores its application to both conventional and multimodal literacies within the classroom.…”
Section: Resultsmentioning
confidence: 99%
“…Research has suggested that when teachers are integrating technology into classrooms, they are doing so to pursue traditional academic tasks rather than new text forms afforded by digital tools (Hutchison & Reinking, 2011;Peterson & McClay, 2012). Although students, particularly preadolescent students, may be using digital tools more in the classroom, they have particular difficulty in gathering information from multimodal texts and are inexperienced at creating, rather than consuming information, with media (Hutchison, Woodward, & Colwell, 2016).…”
Section: Relevant Literaturementioning
confidence: 99%